Evaluation of Biological and Chemical Fungicides to Control White Rust in Chrysanthemum Grown Under Open Condition - Indijarto Budi Rahardjo; Kurniawan Budiarto; Budi Marwoto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The effort to reduce chemicals has become an important issue in floriculture agribusiness. The chemicals included fungicides for white rust control in chrysanthemum. The combined application of synthetic fungicide with biological agent and botanical fungicide were expected not only to reduce synthetic fungicide application, but also suppressed the white rust attacks. The research was conducted at the Indonesian Ornamental Crops Research Institute (IOCRI). A factorial randomized complete blocked experiment was designed to facilitate combined applications of hexaconazol-50 (SFH-50), antagonist microbe Corynebacterium sp. (Cor-5) and formulated botanical fungicide CEES 50EC (ES-50). The results showed that the combined SFH-50 with Cor-5 and ES-50 merely affected the disease intensity, yet less on white rust incidence, period of disease emergence, plant growth, flower production and quality. All combined applications of SFH-50 with Cor-5 and ES-50 showed lower disease intensity than single SFH-50. Higher suppressions were detected on 1 ml/l SFH-50 + 5 ml/l Cor-5-3 and 1 ml/l SFH-50 + 2 ml/l ES-50-3. The use of antagonist microbe and botanical fungicide singly or in combination with synthetic fungicide could reduce with the higher affectivity than single synthetic fungicide application.